Dampak Psikologis Perawat Dalam Merawat Pasien Covid 19 - Wirmando Wirmando; Yunita Gabriela Madu; Faustino Atbar (Media Keperawatan:Politeknik Kesehatan Makassar, 2022)
Nurses are at the forefront and are currently battling the covid 19 pandemic. They are working under tremendous pressure which puts them at increased disruption. The purpose of this study was to explore the psychological impact experienced by nurses in treating COVID-19 patients. This study is a phenomenological approach. This study was conducted on 5 nurses who treat covid 19 patients. Data collection was carried out using in-depth interviews with semistructured interview guidelines. Data analysis used the technique of Interpretative Analysis Phenomenology (IPA). The results of this study found 5 (five) main themes, 1) worrying about yourself and others in caring for covid 19 patients, 2) sad because they had to be quarantined and separated from family, 3) experiencing emotional disturbances, 4) feeling stressed and depressed, and 5) withdraw from the environment. Nurses experience psychological impacts in caring for COVID-19 patients which can affect the quality of nursing care provided. Therefore, it is necessary for hospitals to prepare physically and mentally nurses before entering COVID-19 patients, and it is also necessary to have encouragement and emotional support in order to provide the psychological impact experienced by nurses.